Reducing Environmental Tobacco Smoke Exposure of Preschool Children: A Randomized Controlled Trial of Class-Based Health Education and Smoking Cessation Counseling for Caregivers - Wang, Yun (MDPI, 2015)
Objectives: To assess counseling to caregivers and classroom health education interventions to reduce environmental tobacco smoke exposure of children aged 5–6 years in China. Methods: In a randomized controlled trial in two preschools in Changsha, China, 65 children aged 5–6 years old and their smoker caregivers (65) were randomly assigned to intervention (n = 33) and control (no intervention) groups (n = 32). In the intervention group, caregivers received self-help materials and smoking cessation counseling from a trained counselor, while their children were given classroom-based participatory health education. Children’s urinary cotinine level and the point prevalence of caregiver quitting were measured at baseline and after 6 months. Results: At the 6-month follow-up, children’s urinary cotinine was significantly lower (Z = –3.136; p = 0.002) and caregivers’ 7-day quit rate was significantly higher (34.4% versus 0%) (p < 0.001; adjusted OR = 1.13; 95% CI: 1.02–1.26) in the intervention than control group. Conclusions: Helping caregivers quitting smoke combined with classroom-based health education was effective in reducing children’s environmental tobacco smoke exposure. Larger-scale trials are warranted.